Effectiveness of the YourCall™ text message intervention to reduce harmful drinking in patients discharged from trauma wards: protocol for a randomised controlled trial. (December 2017) - Ameratunga, Shanthi; Kool, Bridget; Sharpe, Sarah; Reid, Papaarangi; Lee, Arier; Civil, Ian; Smith, Gordon; Thornton, Vanessa; Walker, Matthew; Whittaker, Robyn
Abstract Background Behavioural brief interventions (BI) can support people to reduce harmful drinking but multiple barriers impede the delivery and equitable access to these. To address this challenge, we developed YourCall™, a novel short message service (SMS) text message intervention incorporating BI principles. This protocol describes a trial evaluating the effectiveness of YourCall™ (compared to usual care) in reducing hazardous drinking and alcohol related harm among injured adults who received in-patient care. Methods/design Participants recruited to this single-blind randomised controlled trial comprised patients aged 16-69 years in three trauma-admitting hospitals in Auckland, New Zealand. Those who screened positive for moderately hazardous drinking were randomly assigned by computer to usual care (control group) or the intervention. The latter comprised 16 informational and motivational text messages delivered using an automated system over the four weeks following discharge. The primary outcome is the difference in mean AUDIT-C score between the intervention and control groups at 3 months, with the maintenance of the effect examined at 6 and 12 months follow-up. Secondary outcomes comprised the health and social impacts of heavy drinking ascertained through a web-survey at 12 months, and further injuries identified through probabilistic linkage to national databases on accident insurance, hospital discharges, and mortality. Research staff evaluating outcomes were blinded to allocation. Intention-to-treat analyses will include assessment of interactions based on ethnicity (Māori compared with non-Māori). Discussion If found to be effective, this mobile health strategy has the potential to overcome current barriers to implementing equitably accessible interventions that can reduce harmful drinking. Trial registration Universal Trial Number (UTN) U1111-1134-0028.ACTRN12612001220853 . Submitted 8 November 2012 (date of enrolment of first participant); Version 1 registration confirmed 19 November 2012. Retrospectively registered.